Pengaruh Kemampuan Teknik Personal dan Dukungan Manajemen Terhadap Kinerja SIA dengan Motivasi Kerja Sebagai Pemoderasi - Parwa, I Putu Kurnia Adhi; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi, 2019)
Accounting information system performance is a reflection of the level of achievement in using accounting information systems within a certain period. This research aims to know the influence of personal skills and top management supporton accounting information systems performance with the motivation of working as moderation variabel. The population in this research is all employees who us e accounting information systemin the 26 head office BPR in Gianyar Regency. The sample selection technique used in this research is the purposive sampling technique. Respondents used in this research amounted to 78 respondent. Data analysis technique used in this research is MRA. Based on the results of the analysis it was found that the ability of personal techniques and topmanagement support has a positive effect on accounting information system performance and motivation of working is able to strengthen the relationship of the ability of personal techniques and topmanagement support on accounting information system performance. Keywords: Ability of personal techniques ; topmanagement support ; motivation of working;  accounting information system performance.